2005
DOI: 10.1385/abab:121:1-3:0243
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucosidase Production by <I>Trichoderma reesei</I>

Abstract: The hydrolysis of cellulose to the water-soluble products cellobiose and glucose is achieved via synergistic action of cellulolytic proteins. The three types of enzymes involved in this process are endoglucanases, cellobiohydrolases, and beta-glucosidases. One of the best fungal cellulase producers is Trichoderma reesei RUT C30. However, the amount of beta-glucosidases secreted by this fungus is insufficient for effective cellulose conversion. We investigated the production of cellulases and beta-glucosidases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 0 publications
2
6
0
1
Order By: Relevance
“…The maximum filter paper activity value was obtained when the concentration of buffer arise to 100 mM. In contrast, citrate buffered culture presented the inverse trend, the higher citrate buffer concentration the lower the filter paper activity, which is in accordance with Juhász et al (2005), who tested different Tris-maleate buffer concentrations and shows that the higher the buffer concentration the lower the filter paper activity at day 5 of cultivation. In the present work, it was observed that the influence of buffer concentration in filter paper activity is depending on the buffer used for medium supplementation.…”
Section: Protein and Enzyme Productionsupporting
confidence: 86%
See 2 more Smart Citations
“…The maximum filter paper activity value was obtained when the concentration of buffer arise to 100 mM. In contrast, citrate buffered culture presented the inverse trend, the higher citrate buffer concentration the lower the filter paper activity, which is in accordance with Juhász et al (2005), who tested different Tris-maleate buffer concentrations and shows that the higher the buffer concentration the lower the filter paper activity at day 5 of cultivation. In the present work, it was observed that the influence of buffer concentration in filter paper activity is depending on the buffer used for medium supplementation.…”
Section: Protein and Enzyme Productionsupporting
confidence: 86%
“…T. reesei produces an extracellular, stable, and efficient cellulase enzyme system (Tengborg et al 2001;Lynd et al 2002). T. reesei Rut C-30 is a partially catabolite derepressed, hypercellulolytic mutant strain, widely studied, with improved enzyme production capabilities, when compared to the wild-type and some other strains (Xiong et al 2004;Juhász et al 2005).…”
Section: *Corresponding Authormentioning
confidence: 99%
See 1 more Smart Citation
“…To maintain a constant pH (5.8) in the flasks, a 0.1 M Tris base-maleic acid buffer system was applied [1,22]. After inoculation, the flasks were incubated for 8 days at 28°C and 250 rpm.…”
Section: Enzyme Production In Shake Flasksmentioning
confidence: 99%
“…However, it has also been reported that the amount of β-glucosidase in the culture filtrate of T. reesei Rut C30 may depend on the pH of the culture [37][38][39][40]. In this work, it was possible to obtain enzyme pools with rather significant β-glucosidase content, up to 0.62 IU/mL, in buffered medium containing lactose with an initial pH of 6.0 and a final pH of 5.8.…”
Section: Effect Of Different Carbon Sources and Ph Control On The Promentioning
confidence: 79%